Development of Pop Up Books for Thematic Learning of the Sub-theme of Changes in the Form of Objects - APRILIA, LENNY; IDA PUTRIANI; SRIPIT WIDIASTUTI (Universitas Islam Balitar, 2024)
Limited media facilities and infrastructure for technology-based media in schools require teachers to use print-based media. Students have difficulty understanding thematic learning because of the limitations of interactive media. This research aims to develop pop up book media for thematic learning on the sub-theme of changing the shape of objects that is suitable for use. This research design uses the Borg n Gall's development type up to the evaluation stage. The results of the material expert assessment obtained a percentage of 91.4% with a very feasible category. The results of linguist's assessment got 83.4% categorized feasible. The results of media expert's assessment get 95% it means feasible. Readability of student's test got a percentage of 100% with a very decent category. Student's can read and use pop up books. Readability of teacher's test got 100% with very feasible. So that's pop up book can help teachers in the learning process.